KORELASI TERPAAN MEDIA KIE (KOMUNIKASI, INFORMASI DAN EDUKASI) PENANGGULANGAN HIV DAN AIDS DENGAN TINGKAT PENGETAHUAN PEKERJA SEKS PEREMPUAN (Studi Kasus Pekerja Seks Perempuan Kabupaten Malang) - Setiyaningsih, Lian Agustina (Universitas Merdeka Malang, 2017)
This study discusses the relationship of media exposure to HIV and AIDS IEC (leafflet and stickers) to the level of knowledge of female sex workers in Malang Regency Suko localization. Media IEC is media Information, Education, Communication and leaflet and stickers that are health communication media has been running from 2006 to the present. Media leaflet and stickers is a health communications media that shape and change the knowledge of female sex workers.IEC media exposure and stickers leaflet measured from the frequency and duration of female sex workers in using the media. To measure knowledge of causes, symptoms or signs, treatments, modes of transmission and prevention of HIV and AIDS. The indicators in terms of content and the physical media IEC leaflet and stickers. This study classified as quantitative studies that measure the correlation of the independent variable exposure to media IEC (leaflet and stickers) with the independent variable is the level of knowledge. To determine the relationship between them, this study used the instrument in the form of a questionnaire distributed to 90 female sex workers in the localization Suko. It also uses techniques of data analysis techniques Spearman Rank correlation because not distributed normally. This study proves the existence of a significant correlation between media exposure to HIV and AIDS IEC (leaflet and stickers) with the level of knowledge of female sex workers in Malang Regency Suko localization. Correlations that occur in this study is a positive correlation in which the low correlation coefficient value (p) of +0.362. The coefficient of determination (contribution) in this study is 13.7%. Key words: IEC Media Exposure, The level of Knowledge, and Female Sex WorkersDOI :Â https://doi.org/10.26905/nomosleca.v3i1.1484